Respuesta :

[tex]x^2+12x+43=0 [/tex] 

[tex]x= \dfrac{-b+ \sqrt{b^2-4ac} }{2a}, \dfrac{-b- \sqrt{b^2-4ac} }{2a}[/tex] 

[tex]x= \dfrac{-12+ \sqrt{12^2-4*43} }{2} [/tex],[tex]\dfrac{-12- \sqrt{12^2-4*43} }{2}[/tex] 

[tex]x= \dfrac{-12+2 \sqrt{7i} }{2}, \dfrac{-12-2 \sqrt{7i} }{2}[/tex] 

[tex]x=-6+ \sqrt{7i},-6- \sqrt{7i} [/tex]
x²+12x+43=0

This a quadratic equation ax²+bx+c=0 (in our case a=1, b=12, & c=43)

to solve it, means to calculate the value of x which render this equation nil

In short we have to find the roots x' & x'' by applying the following formula:

x' = [-b+√(b² - 4ac)] / 2a  & x" =[-b - √(b² - 4ac)] / 2a 
If you plug the related values you will notice the amount inside the radical (√)
is negative. As you know such an amount should be positif, hence their is no roots & consequently no solution